2009
DOI: 10.1007/s00330-009-1542-z
|View full text |Cite
|
Sign up to set email alerts
|

Nontumorous arterioportal shunts in the liver: CT and MRI findings considering mechanisms and fate

Abstract: The intrahepatic non-tumorous arterioportal shunt (APS) is one of the important causes of transient hepatic enhancement differences (THED) on dynamic CT or MRI. Most small APSs are located in the peripheral portion of the liver. Because of the parenchymal distortion in the advanced cirrhotic liver, many small APSs tend to show an amorphous or nodular appearance, making them difficult to distinguish from hypervascular tumors. In addition to the use of dynamic CT or MRI, iso-attenuation densities or iso-intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 38 publications
0
36
0
1
Order By: Relevance
“…30% of patients had the most lesions noted on the noncontrast phase and 30% had the most lesions detected on the hepatic arterial phase than on any other phase; moreover, in 6% (2/31) of the patients, hepatic lesions were seen exclusively on the hepatic arterial phase. Even though it has been reported that most hypervascular metastases are seen on the arterial phase of contrast, it is difficult to determine whether the hypervascular lesions represent true metastases or small transient hepatic arterial perfusion abnormalities caused by arterial portal venous shunting [6,13]. …”
Section: Discussionmentioning
confidence: 99%
“…30% of patients had the most lesions noted on the noncontrast phase and 30% had the most lesions detected on the hepatic arterial phase than on any other phase; moreover, in 6% (2/31) of the patients, hepatic lesions were seen exclusively on the hepatic arterial phase. Even though it has been reported that most hypervascular metastases are seen on the arterial phase of contrast, it is difficult to determine whether the hypervascular lesions represent true metastases or small transient hepatic arterial perfusion abnormalities caused by arterial portal venous shunting [6,13]. …”
Section: Discussionmentioning
confidence: 99%
“…As liver cirrhosis progresses, APS via the trans-sinusoidal route can increasingly occur, which is thought to be related to cirrhosis-induced sinusoidal capillarization and obliteration of hepatic venules [82]. In addition, although APS are typically seen as subcapsular wedge-or triangular-shaped transient parenchymal enhancements on the HAP, APS in the cirrhotic liver tend to show a centrally located, round or oval appearance more frequently than those in the non-cirrhotic liver due to the architectural distortion of the background hepatic parenchyma, making the differentiation from HCCs difficult [83]. As a misdiagnosis of hypervascular pseudolesions as HCCs can lead to unnecessary treatment, the differentiation between these two disease entities is of importance in clinical practice.…”
Section: Hcc Vs Hypervascular Pseudolesionsmentioning
confidence: 99%
“…In patients with cirrhosis, the arterioportal shunt is usually found on the arterial phase of a CT scan. The mechanism underlying such an arterioportal shunt is not clear, but it is thought that distortion and capillarization of the hepatic sinusoid disturbs hepatic venular flow and increases intrahepatic vascular resistance, resulting in the arterial blood flow regurgitating to the PV via the arterioportal shunt [75]. Although the arterioportal shunt has minimal clinical significance, it can be mistaken for a small HCC on the arterial phase of a CT scan.…”
Section: Hemodynamic Changesmentioning
confidence: 96%